Effect of pre-sowing electromagnetic treatment on seed germination and seedling growth in maize (zea mays l.) (2011)
The application of magnetic fields appears to produce changes in some physiological processes of plants, including encouraging their development. This study reports the effects of different intensities of electromagnetic fields generated by a solenoid with a variable horizontal magnetic field on the germination and growth of maize seeds. We worked with the experimental seed hybrid San Jose, which was exposed to electromagnetic fields of 0, 2, 4 and 6 mT for 3 min, using a completely randomized design with two seed conditions: imbibed and non-imbibed. Analysis of variance was performed for the variables germination and growth, with a level of significance of 95%; increases were observed in germination, vigor index I, vigor index II and root length, 3, 20, 34 and 23% respectively, compared to the control seeds (untreated) on the eighth day. Similarly, the presence of chlorophyll pigments and carotenoids was assessed and an increase was found in the concentration of chlorophyll a, chlorophyll b and carotene in corn seedlings grown from electromagnetically treated seeds. The response varied depending on the magnetic induction, without any particular trend, the best treatment was 4 μT for 3 min of exposure. The improvement of the evaluated functional variables suggests that the seeds may perform better with an electromagnetic field treatment.